2021
DOI: 10.26833/ijeg.658377
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of urbanization on land surface temperature example of Bursa

Abstract: Land surface temperature (LST) Urban heat island (UHI) Normalized differential vegetation index (NDVI) Bursa Today, industrialization and urbanization in large cities cause an increase in the surfaces covered with man-made objects such as concrete and asphalt. The expansion of urban areas and increase in the using materials with high heat storage properties, directly affect the Land Surface Temperature (LST), which shows an increase in the sensible temperature of the region. LST is directly connected to the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
(13 reference statements)
1
4
1
Order By: Relevance
“…Many studies have shown an 'urban heat island effect' as a common outcome of urbanization (Battles and Kolbe, 2019;Yamak et al, 2021). However, we find no evidence of elevated…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Many studies have shown an 'urban heat island effect' as a common outcome of urbanization (Battles and Kolbe, 2019;Yamak et al, 2021). However, we find no evidence of elevated…”
Section: Discussioncontrasting
confidence: 83%
“…Land Surface Temperature (LST) is typically higher in urban areas, resulting in what is known as the urban heat island effect (Peng et al, 2012;Lee et al, 2014). Several studies associate the reduction of vegetation and increase in LST as an immediate effect of urbanization (Nalini, 2021;Yamak et al, 2021). An increase in LST could, however, be beneficial to some species; for example, the increase in grey-headed flying foxes Pteropus poliocephalus that roost in Melbourne has been attributed to higher urban temperatures (Parris and Hazell, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…When considering urban environments and opportunities for work, education, health, and housing (Haddad & Aouachria, 2015;Yamak et al, 2021), the need for the development of mobility mechanisms is increasing, especially in view of its purpose of facilitating "the displacement of people and goods in the city due to its complex activities" (Araujo et al, 2011).…”
Section: Urban Heat and Mobilitymentioning
confidence: 99%
“…Therefore, several studies on lake's water temperature had been conducted. Yamak and Comert [27] used Landsat images for the extraction of the Land Surface Temperature (LST) map, and low LST values were observed in vegetated areas, forest areas, and wetlands. In the study of Xie et al [28], MODIS LST data were used to examine the spatial and temporal variations in lake surface water temperature (LSWT) of China's lakes between 2001 and 2016.…”
Section: Introductionmentioning
confidence: 99%